2015
DOI: 10.1590/2176-9451.20.2.049-054.oar
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bleaching and desensitizing gel on bond strength of orthodontic brackets

Abstract: OBJECTIVE: The objective of this study was to assess, in vitro, the influence of bleaching gel and the use of desensitizing agent over bond strength of ceramic brackets bonded to bovine enamel. METHODS: One hundred bovine incisors were selected and randomly divided into five groups (n = 20): Group 1, control group (without bleaching); Group 2, bleached with 35% hydrogen peroxide; Group 3, bleached with 35% hydrogen peroxide (three applications, 15 minutes each) and desensitizing agent applied for 10 minutes; G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Bleaching agents also affect the collagen network of dentin, resulting in denaturing and relative instability of the dentin organic matrix, thereby decreasing the bond strength. 4 In addition, TBS values of a group undergoing 40% MP extract treatment reached a level almost equal to those of the NC group. It is suggested that treatment with MP extract could approximate the bond strength values of teeth which had not experienced the bleaching procedure.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Bleaching agents also affect the collagen network of dentin, resulting in denaturing and relative instability of the dentin organic matrix, thereby decreasing the bond strength. 4 In addition, TBS values of a group undergoing 40% MP extract treatment reached a level almost equal to those of the NC group. It is suggested that treatment with MP extract could approximate the bond strength values of teeth which had not experienced the bleaching procedure.…”
Section: Discussionmentioning
confidence: 91%
“…2,3 The number of patients seeking orthodontic treatment who might have a history of tooth bleaching is increasing because, following previous procedures, they usually tend to be conscious of orthodontic problems and desire treatment. 4 Unfortunately, bleaching may lead to a reduction in orthodontic bracket bond strength. [5][6][7] In-office bleaching can produce a direct result including residual peroxide on the tooth surface which might inhibit the polymerization of the adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in enamel microhardness may be explained by mineral loss from enamel after bleaching procedures, Preliminary studies reported that the application of peroxides could reduce the calcium and phosphate enamel content, as well as its fluoride concentration. 12,14,16,20 It is widely accepted that, surface hardness is used as a characteristic property to determine mineral loss, because it is an established technique for evaluating the mineralization rate of enamel. 17 Beside this, carbopol, which is the thickening agent in most bleaching agents, can decrease the enamel microhardness during bleaching, as carbopol's high calcium-binding capacity and inhibits hydroxyapatite crystal growth.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is advised to delay bonding to bleached enamel for at least one week after completion of bleaching process to eliminate or reduce the effects of residual oxygen. Within this period, residual oxygen must have been neutralized, thus not interfering with polymerization of resin composite for bonding 16,47 According to Al-Salehi et al 48 there is direct proportional relationship between mineral loss and bleaching agent concentration. As they pointed out that bleaching agents based on 35-38% hydrogen peroxide showed significantly higher values of calcium loss compared to at-home gels (10% carbamide peroxide).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation